Design and implementation of tailored intervention to increase vaccine acceptance in a Somali community in Stockholm, Sweden - based on the Tailoring Immunization Programmes approach - Asha Jama; Emma Appelqvist; Asli Kulane; Susanne Karregård; Johanna Rubin; Sahar Nejat; Katrine Bach Habersaat; Cath Jackson; Robb Butler; Ann Lindstrand; Karina Godoy-Ramirez (Public Health in Practice, 2022)
Objectives: Sweden has had a high and stable vaccination coverage for measles-mumps-rubella (MMR) vaccine (>96%) through the national immunization program (NIP), but coverage rates highlight local pockets of lower vaccination coverage. This project addressed low MMR vaccine acceptance among parents in a Somali community, in Stockholm. The objective of the intervention was to increase vaccine confidence and MMR-vaccine uptake and also to inform practices addressing vaccine acceptance. Study design: This paper describes the design and implementation of a multi-component intervention based on the Tailoring Immunization Programmes (TIP) approach, developed by the WHO European Regional Office. Methods: The theoretical underpinning of TIP is the Capability, Opportunity, and Motivation Model (COM-B model) and Behaviour Change Wheel framework (BCW), adapted for vaccination. The COM-model was used to identify barriers and drivers to vaccination and intervention types. The TIP-phases described in this paper are: pre-TIP (planning), three succeeding TIP phases (situational analysis, formative research, intervention design) and the post-TIP phase (implementation). Results: The situation analysis and formative research revealed that parents feared the MMR vaccine due to autism or that their child would stop talking following vaccination, despite lack of scientific evidence for an association between autism and MMR vaccines. Barriers were linked to their associated COM-B factors and mapped to appropriate intervention types for two target groups: Somali parents and nurses at the Child Health Centres (CHC). Selected intervention types targeting parents were education, persuasion and modelling whereas education and training were selected for CHC nurses. The intervention activities included community engagement for parents, while the activities for nurses focused on improving encounters and dialogue with parents having low vaccine acceptance. Following the intervention design the activities were developed, pilot tested and implemented. Conclusion: This study confirm that the TIP approach is valuable for guiding a stepwise working process for a thorough understanding of barriers and drivers for MMR vaccination among parents in this Somali community. It facilitated the design of a theory and evidence-informed intervention targeting parents and nurses.